Answer:
y = -3x
Step-by-step explanation:
Slope is -3
If the discriminant, b² - 4ac is<u> positive</u>
<h3>How to complete the statement?</h3>
From the question, we have the following equation of discriminant
The discriminant (d) is calculated as
d = b² - 4ac
The solutions of a quadratic equation are dependent on the following conditions
- If d = 0, the quadratic equation has 1 real solution
- If d < 0, the quadratic equation has imaginary solutions
- If d > 0, the quadratic equation has 2 different real solutions
This means that "d > 0, the quadratic equation has 2 different real solutions" implies that the discriminant is positive
Hence, the complete statement is (b) positive
Read more about discriminant at
brainly.com/question/64103
#SPJ1
Given:
- The product of two numbers is (-9/16).
- One of the numbers is (-4/15)
To find: The other number.
Answer:
Let's assume the unknown number to be 'x'.
(-4/15) × x = (-9/16)
× = (-9/16) ÷ (-4/15)
When we divide a fraction by another fraction, the divisor will be taken in its reciprocal form.
x = (-9/16) × (-15/4)
x = 135/64
Therefore, the other number is 135/64.
Hope it helps. :)
Answer:
(i) (f - g)(x) = x² + 2·x + 1
(ii) (f + g)(x) = x² + 4·x + 3
(iii) (f·g)(x) = x³ + 4·x² + 5·x + 2
Step-by-step explanation:
The given functions are;
f(x) = x² + 3·x + 2
g(x) = x + 1
(i) (f - g)(x) = f(x) - g(x)
∴ (f - g)(x) = x² + 3·x + 2 - (x + 1) = x² + 3·x + 2 - x - 1 = x² + 2·x + 1
(f - g)(x) = x² + 2·x + 1
(ii) (f + g)(x) = f(x) + g(x)
∴ (f + g)(x) = x² + 3·x + 2 + (x + 1) = x² + 3·x + 2 + x + 1 = x² + 4·x + 3
(f + g)(x) = x² + 4·x + 3
(iii) (f·g)(x) = f(x) × g(x)
∴ (f·g)(x) = (x² + 3·x + 2) × (x + 1) = x³ + 3·x² + 2·x + x² + 3·x + 2 = x³ + 4·x² + 5·x + 2
(f·g)(x) = x³ + 4·x² + 5·x + 2
Answer: <em>3w+4b</em>
Step-by-step explanation:
<em>Take your given equation</em>
<em>w+w+w+b+b+b+b</em>
<em>There are 3 w's and 4 b's</em>
<em>Combine like terms</em>
<em>w+w+w=</em><em>3w</em>
<em>b+b+b+b=</em><em>4b</em>
<em>3w+4b</em>